A Centimeter-Sized Quaternary Ti-Zr-Be-Ag Bulk Metallic Glass. (28th April 2014) - Zhao, S. F.; Shao, Y.; Gong, P.; Yao, K. F.
Abstract : A novel centimeter-sized Ti-based bulk metallic glass (BMG) was developed by the addition of Ag in the ternary Ti41 Zr25 Be34 glassy alloy. By replacing Be with Ag, the glass forming ability (GFA), the yield strength, and the supercooled liquid temperature of the quaternary Ti 41 Zr 25 Be 34−x Ag x (x = 2, 4, 6, 8 at.%) glassy alloys have been obviously enhanced. Among the developed Ti-Zr-Be-Ag alloy systems, the Ti41 Zr25 Be28 Ag6 alloy possesses the largest critical diameter (D max ) of 10 mm, while the yield strength is also enhanced to 1961 MPa, which is much larger than that of Ti41 Zr25 Be34 (1755 MPa) alloy. The experimental results show that Ag is an effective element for improving the GFA and the yield strength of Ti-Zr-Be glassy alloy.